Regeneration of inorganic nutrient in eutrophic environment by a bacterium, Xanthomonas sp. - Karim, Md Abdul; Happy, Rehena Nasrin (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 42(1): 123-127, 2014